Job burnout and quiet quitting in Vietnamese banking sector: the moderation effect of optimism - Pham Thu Trang; Nguyen Thi Thu Trang (Cogent Business & Management, 2024)
While the connection between job burnout and quiet quitting is evident, the inhibitor underlying this relationship remains elusive. This research explores the moderating effect of optimism – a personal resource on the relationship between job burnout and quiet quitting. This study utilized a survey method of 405 Vietnamese employees working in 19 Vietnamese banks and analyzed data using PLS-SEM via Smart PLS 4.0. The results reveal that three dimensions of job burnout, namely personal burnout, work-related burnout, and client-related burnout, positively impact quiet quitting. In addition, optimism negatively moderates the links between personal burnout and work-related burnout with quiet quitting. Unexpectedly, optimism does not moderate the linkage between client-related burnout and quiet quitting. These results offer practical implications for human resource practices within Vietnamese banks.
Keywords: 650; Job burnout; quiet quitting; optimism; banking; Vietnam